Relación entre hipomineralización incisivo molar en niños de 6–11 años y el sexo del IEPM N° 601457 - Leoncio Prado - Del Carpio Ardaya, Layza (2025)
This study aimed to determine the relationship between Molar-Incisor Hypomineralization (MIH) and sex in schoolchildren aged 6 to 11 years from IEPM No. 601457 – Leoncio Prado. A quantitative, non-experimental, cross-sectional, and correlational study was carried out in a sample of 54 schoolchildren selected according to inclusion criteria, applying the diagnostic criteria of the European Academy of Pediatric Dentistry (EAPD). Data were analyzed through descriptive and inferential statistics using the chi square test with a 5% significance level. The prevalence of MIH was 20.5 %; among affected children, 55.6% presented mild lesions, 40.7% moderate, and 3.7% severe. The mean age was 8.57 years, with a balanced distribution between males (46.3%) and females (53.7%). No statistically significant association was found between MIH severity and sex (p=0.805), nor between severity and age (p=0.390). It is concluded that MIH was present in a considerable proportion of schoolchildren, mainly in mild and moderate forms, with no significant relationship with sex or age, partially consistent with previous studies in similar populations. These findings highlight the need to strengthen early diagnostic strategies and preventive measures in children to minimize later complications such as enamel fractures, dental sensitivity, and increased susceptibility to caries.